2015
DOI: 10.1111/jam.12723
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graded levels of tannin-containing tropical tree leaves on in vitro rumen fermentation, total protozoa and methane production

Abstract: Ficus bengalensis, Au. integrifolis and Az. indica leaves are of interest in the enteric methane ameliorative strategies. Total mixed ration containing 10-15% ground F. bengalensis or Au. integrifolis or Az. indica leaves could be fed to ruminants to reduce enteric methanogenesis. However, in vivo trials need to be carried out to validate these in vitro results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 26 publications
3
51
0
7
Order By: Relevance
“…Inhibition of this symbiotic relationship may also negatively impact the ciliated protozoa population. Bhatta et al (2015) determined that rumen ciliated protozoa populations decreased when the feedstuff contained CT from Ficus bengalensis and Azardirachta indica at concentrations of 26 and 13.8%, respectively.…”
Section: Ct-enteric Fermentation Interactionsmentioning
confidence: 99%
“…Inhibition of this symbiotic relationship may also negatively impact the ciliated protozoa population. Bhatta et al (2015) determined that rumen ciliated protozoa populations decreased when the feedstuff contained CT from Ficus bengalensis and Azardirachta indica at concentrations of 26 and 13.8%, respectively.…”
Section: Ct-enteric Fermentation Interactionsmentioning
confidence: 99%
“…Therefore, mitigation of CH 4 production by ruminants has been recognised as an important goal because it reduces the greenhouse gas (GHG) emission and improves feed efficiency (Bouchard et al 2015). Enteric CH 4 is a by-product of anaerobic fermentation in the rumen which is produced by methanogenic archaea for disposing metabolic hydrogen (H 2 ) produced by their metabolic activity (Bhatta et al 2014). In the rumen ecosystem, rumen protozoa are also involved in methanogenesis through a symbiotic relationship with methanogenic archaea which utilise H 2 produced by the protozoa to produce CH 4 (Tan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Suharyono & Widiawati (2007) also reported that molasses is easily digested carbohydrates which are major feed for protozoa. Bhatta et al (2015) also reported that methane production was related to the protozoa population. Methane was generated by methanogens bacteria that consumed hydrogen.…”
Section: In Vitro Gas Characteristicsmentioning
confidence: 95%